Distributive Implications of Fertility Changes in Latin America - Badaracco, Nicolás (2016)
Fertility rates significantly fell over the last decades in Latin America. In order to assess the extent to which these changes contributed to the observed reduction in income poverty and inequality we apply microeconometric decompositions to microdata from national household surveys from seven Latin American countries. We find that changes in fertility rates were associated to a non-negligible reduction in inequality and poverty in the region. The main channel was straightforward: lower fertility implied smaller families and hence larger per capita incomes. Lower fertility also fostered labor force participation, especially among women, which contributed to the reduction of poverty and inequality in most countries, although the size of this effect was smaller.